The preventive check in medieval and pre-industrial England - Morgan Kelly; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2011)
England's post-Reformation demographic regime has been characterized as low pressure. Yet the evidence hitherto for the presence of a preventive check, defined as the short-run response of marriage and births to variations in living standards, is rather weak. New evidence in this paper strengthens the case for the preventive check in both medieval and early modern England. We invoke manorial data to argue the case for a preventive check on marriages in the middle ages. Our analysis of the post-1540 period, based on parish-level rather than aggregate data, finds evidence for a preventive check on marriages and births.
Keywords: 330